2011
DOI: 10.1080/16506073.2011.616217
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Improved Shooting Precision in Biathlon After 10 Weeks of Combined Relaxation and Specific Shooting Training

Abstract: The aim of this study was to test the hypothesis that a combined relaxation (applied tension release, ATR) and specific shooting training regimen may enhance shooting ability of biathlon athletes. Seven biathletes of high national level were randomized into an experimental group (age 20 ± 5 years; Vo2max 60 ± 8 mL kg(-1) min(-1)) and were asked to add this special training intervention to their regular training for 10 weeks, while five other biathletes served as controls (age 19 ± 2 years; Vo2max 57 ± 10 mL kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
2
19
0
2
Order By: Relevance
“…Postural balance, mainly in the shooting direction, was related to the cleanness of triggering and vertical holding ability Laaksonen et al . (2011) 68 To test the hypothesis that combined relaxation and specifically designed shooting training enhance shooting by biathletes 20 subjects (13 males, 7 females) at the national and international (up to World Cup) levels; age: 20 years for the experimental group and 19 years for the control group Combined relaxation and specific shooting training (holding and routine shooting maneuvers without ammunition) enhanced shooting performance Larue et al (1989) 110 To compare the body–gun stability of biathletes and rifle shooters in the standing position 8 subjects: 2 experts and 2 novice rifle shooters, 2 experts and 2 novice biathlon shooters Expert biathlete and rifle shooters use different strategies regarding rifle oscillation and center-of-pressure-displacement, adapting to their respective disciplines Niinimaa and McAvoy (1983) 40 To analyze stance stability while standing at rest with and without aiming an air rifle. Body sway was measured at rest and after a bout of simulated cross-country ski racing 16 males subjects: a control group with no previous shooting experience, groups of rookie and established biathletes, and experienced rifle shooters Body sway was greater during aiming than while simply standing at rest, and also greater during aiming after exercise than at rest.…”
Section: Biathlon Shooting Techniquementioning
confidence: 99%
“…Postural balance, mainly in the shooting direction, was related to the cleanness of triggering and vertical holding ability Laaksonen et al . (2011) 68 To test the hypothesis that combined relaxation and specifically designed shooting training enhance shooting by biathletes 20 subjects (13 males, 7 females) at the national and international (up to World Cup) levels; age: 20 years for the experimental group and 19 years for the control group Combined relaxation and specific shooting training (holding and routine shooting maneuvers without ammunition) enhanced shooting performance Larue et al (1989) 110 To compare the body–gun stability of biathletes and rifle shooters in the standing position 8 subjects: 2 experts and 2 novice rifle shooters, 2 experts and 2 novice biathlon shooters Expert biathlete and rifle shooters use different strategies regarding rifle oscillation and center-of-pressure-displacement, adapting to their respective disciplines Niinimaa and McAvoy (1983) 40 To analyze stance stability while standing at rest with and without aiming an air rifle. Body sway was measured at rest and after a bout of simulated cross-country ski racing 16 males subjects: a control group with no previous shooting experience, groups of rookie and established biathletes, and experienced rifle shooters Body sway was greater during aiming than while simply standing at rest, and also greater during aiming after exercise than at rest.…”
Section: Biathlon Shooting Techniquementioning
confidence: 99%
“…Indeed, many world-class biathletes now focus especially on preparing rapidly for the first shot and leaving the shooting lane as quickly as possible. Shooting at rest as well as shooting without ammunition (so-called dry shooting) can also improve triggering behavior, rifle stability, and/or holding ( Groslambert et al, 2003 ), as well as mental aspects of shooting ( Laaksonen et al, 2011 ). Thus, training under conditions that resemble competitive shooting is recommended for elite biathletes, not only to improve the accuracy but also to minimize the loss of time on the range and while shooting.…”
Section: Training For Olympic Biathlon Racesmentioning
confidence: 99%
“…Elite‐level biathletes have shown better stability of hold compared to youth‐level biathletes in standing shooting without physical stress, which contributed to the observed shooting performance difference between the different age groups . Two training intervention studies in biathlon shooting have also shown that specific shooting training can improve stability of hold and biathlon standing shooting performance both in rest and after intense exercise …”
Section: Introductionmentioning
confidence: 99%
“…biomechanics, optoelectronic measures, performance, postural balance, technique in biathlon shooting have also shown that specific shooting training can improve stability of hold 4 and biathlon standing shooting performance both in rest and after intense exercise. 5 In order to achieve a stable hold in biathlon standing shooting, good postural balance is required. The stability of hold in biathlon standing shooting has been related to postural balance both in rest and after intense exercise.…”
Section: Introductionmentioning
confidence: 99%